Analysis of the biochemical composition of cranberry natural enrichments intended for use in health food technologies - Stetsenko, Natalia; Goyko, Iryna (My University, 2019)
In the work the prospects of using cranberry products in technologies of wellnessproducts are substantiated. The content of biologically active compounds in fresh berries and their effect on the human body are considered on the basis of the analysis of literature sources. Methods of obtaining puree and powder of cranberry berries are proposed, their physical-chemicalproperties and biochemical composition are investigated. The content of functional ingredients infresh berries and obtained natural enrichments is compared. A method of using cranberry powder for the production of health yogurt is suggested.
Keywords: ягоди журавлини; пюре; порошок; натуральний збагачувач; оздоровчий харчовий продукт; йогурт; ягоды клюквы; пюре; порошок; натуральный обогатитель; оздоровительный пищевой продукт; йогурт; cranberries; puree; powder; natural enrichment; health food; yogurt; кафедра технології оздоровчих продуктів